Global Alfvén Wave Power in the Auroral Zone in Relation to the AE Index. Issue 11 (12th November 2019) - Keiling, Andreas; Thaller, Scott; Wygant, John; Dombeck, John
Abstract: The importance of Alfvén waves in energy transport inside the magnetosphere has been demonstrated over the last two decades. Generated in various magnetospheric regions, much of their energy carried to the auroral zone is deposited inside the auroral acceleration region (AAR) via particle acceleration. In this report, we present the integrated contributions of Alfvén wave power to the nightside auroral zone during different levels of auroral activity, as measured by the auroral electrojet ( AE ) index. Data were collected from an ideal vantage point, namely, above the nominal AAR, over a 6‐year period of Polar satellite operation. We provide functional forms for the total inflowing and outflowing Alfvén wave powers, both of which are linear—at least up to an AE index of 700 nT. For all AE values the power inflow is significantly larger than the power outflow; therefore, the estimated net wave power flowing into the AAR is sufficient to account for the integrated precipitating Alfvénic electron power in the nightside auroral zone below the AAR. The estimated global Alfvén wave absorption (by electrons) and reflection are, respectively, 56% and 33% (upper limit), while an excess wave power of 11% (lower limit) is available for other energy conversion processes, such as Joule heating and Alfvénic ion outflow. Key Points: Global Alfvén wave power above the auroral acceleration region can be estimated from the AE index Global Alfvén wave power above the auroral acceleration region can account for the global power of Alfvénic electron precipitation Estimates of global Alfvén wave power absorption and reflection are provided